Growing Red Spinach Microgreens with Various LED Colors and Planting Media - Salsabila Mumtaz Widiyarso; Florentina Kusmiyati; Karno Karno (Institut Pertanian Bogor, 2025)
Red spinach microgreens are green plants that are consumed by their leaves in 14 days harvest time. This study aimed to examine the effects of LED light color and various planting media on the growth of red spinach microgreens. This research was conducted from June 1 to July 22, 2023, at Sendangguwo, at the Laboratory of Plant Ecology and Production, Faculty of Animal Husbandry and Agriculture, Diponegoro University, and at the Chem-mix Pratama Laboratory, Yogyakarta. The experimental design was a divided plot design with triplicates. The main plot was the LED light color treatment with four levels: white, red, blue, and green. The subplots were planting media treatments with 3 levels: soil, cocopeat, and vermiculite. The parameters observed included plant height, root length, wet weight, chlorophyll content, carotenoid content, and vitamin C content. The collected data were analyzed using analysis of variance and further tested using Duncan's Multiple Range test. The results showed that the color of white LED lights can increase chlorophyll and carotenoid contents, and in soil planting media, it also increased chlorophyll and carotenoid contents in red spinach microgreens. Cocopeat planting medium increased plant height, and vermiculite planting medium increased wet weight and vitamin C content. In conclusion, the color treatment of white LED lights and soil growing media increased chlorophyll and carotenoid content in red spinach microgreens. Keywords: LED, microgreens, planting media, red spinach